An Exploring Study on Chinese Sports Law System in Digital Economy - Chen, Hongbing; Wang, Xinghua (Technium Social Sciences Journal, 2022)
China uses digital, intelligent, and networked technology as the foundation for the development of sports at this stage of the global digital economy's rapid expansion. Sports laws support digital applications and guide the direction of sports development. This paper organizes one sports law, one sports law soon to be in force, seven administrative policies, 26 State Council documents, 31 sports departmental policies, 165 normative documents, and 110 sports institutional documents of the General Administration of Sports in China that are currently in effect as of June 30, 2022. Reviewing the existing literature shows that China's digital economy-related sports legislation needs to be revised, sports policies and normative documents replace laws, relevant content is advocacy-oriented, the sports legislative system needs to be completed, and the extensive and complex sports legislative needs cannot be met.